Buletin Peternakan : PRODUKTIVITAS TANAMAN KALIANDRA (Calliandra calothyrsus) SEBAGAI HIJAUAN PAKAN PADA UMUR PEMOTONGAN YANG BERBEDA - Abqoriyah, Ristanto Utomo, Bambang Suwignyo (Peternakan UGM, 2015)
This research aimed to determine the production and nutrient content of calliandra (Caliandra calothyrsus) as a forage for ruminant in the different defoliation time. This research was conducted for 48 weeks (June 2012–June 2013) at Kaligesing forage feed area, Animal Science Department, Purworejo, Central Java. Design of the research was Completely Randomized Block Design. Soil slope was used as block. The research treatments were 6 (P1), 8 (P2), 12 (P3) and 16 (P4) weeks of cutting age. The grass of all treatment groups were cut together at the same day prior to experiment. Caliandra calothyrsus was cut at edible portion. Parameters measured were fresh forage, dry matter, organic matter and crude protein production and also nutrient content namely dry matter, organic matter, crude protein, extract ether, crude fiber, BETN and TDN